Evaluation of Online Information in University Students: Development and Scaling of the Screening Instrument EVON - Hahnel, Carolin; Eichmann, Beate; Goldhammer, Frank (Frontiers in Psychology, 2020)
As Internet sources provide information of varying quality, it is an indispensable prerequisite skill to evaluate the relevance and credibility of online information. Based on the assumption that competent individuals can use different properties of information to assess its relevance and credibility, we developed the EVON (evaluation of online information), an interactive computer-based test for university students. The developed instrument consists of eight items that assess the skill to evaluate online information in six languages. Within a simulated search engine environment, students are requested to select the most relevant and credible link for a respective task. To evaluate the developed instrument, we conducted two studies: (1) a pre-study for quality assurance and observing the response process (cognitive interviews of n = 8 students) and (2) a main study aimed at investigating the psychometric properties of the EVON and its relation to other variables (n = 152 students). The results of the pre-study provided first evidence for a theoretically sound test construction with regard to students’ item processing behavior. The results of the main study showed acceptable psychometric outcomes for a standardized screening instrument with a small number of items. The item design criteria affected the item difficulty as intended, and students’ choice to visit a website had an impact on their task success. Furthermore, the probability of task success was positively predicted by general cognitive performance and reading skill. Although the results uncovered a few weaknesses (e.g., a lack of difficult items), and the efforts of validating the interpretation of EVON outcomes still need to be continued, the overall results speak in favor of a successful test construction and provide first indication that the EVON assesses students’ skill in evaluating online information in search engine environments.